2002
DOI: 10.1177/026988110201600419
|View full text |Cite
|
Sign up to set email alerts
|

The development of a clinical syndrome of asymptomatic pancreatitis and eosinophilia after treatment with clozapine in schizophrenia: implications for clinical care, recognition and management

Abstract: Clozapine, the first atypical antipsychotic, is indicated for the treatment of therapy-resistant schizophrenia. It needs to be monitored closely because of its well-known potential side-effects, especially agranulocytosis. We present a case of a middle-aged woman with chronic schizophrenia, who was treated with clozapine and developed a clinical syndrome of asymptomatic pancreatitis and eosinophilia within the fifth week of treatment. Asymptomatic pancreatitis has rarely been reported up to now and is not reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 6 publications
0
7
2
Order By: Relevance
“…Differently from the cases reported by Bergemann et al [11], Garlipp et al [10], and Sani et al [5], our patient was symptomatic, as the other eleven cases reported in the literature.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Differently from the cases reported by Bergemann et al [11], Garlipp et al [10], and Sani et al [5], our patient was symptomatic, as the other eleven cases reported in the literature.…”
Section: Discussioncontrasting
confidence: 92%
“…Differently from Frankenburg and Kando [8], Chengappa et al [9] and Garlipp et al [10], we did not observe eosinophilia, but this abnormality is by no means the rule with clozapine-associated pancreatitis. Differently from the cases reported by Bergemann et al [11], Garlipp et al [10], and Sani et al [5], our patient was symptomatic, as the other eleven cases reported in the literature.…”
Section: Discussioncontrasting
confidence: 90%
“…This hematological side effect has been found in 0,2 to 61,7% of clozapine-treated patients 2,[4][5][6][7][8][9]15 . The high variability of the reported rates can be attributed to four factors: small samples sizes, differences in patient pools, varied trial lengths and inconsistencies in the definition of this dyscrasia 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In those cases, clozapine's withdrawal was mandatory due to the eosinophilia's life threatening consequences 6,9,12,13,16 . Nevertheless, the possibility of its reintroduction exists even in such cases provided that a close clinical monitoring is mantained 13 .…”
Section: Case Reportmentioning
confidence: 99%
“…Clozapine-associated eosinophilia has been reported in two different forms: transient benign eosinophilia and eosinophilia with end organ damage [13]. Clozapine-associated eosinophilia with end organ damage has reportedly been associated with pancreatitis [4], pleural effusions [5], eosinophilic pneumonia [6], colitis [7], hepatitis [8], and pericarditis [9]. Here we describe a patient with a dramatic eosinophilic response to clozapine resulting in systemic manifestations.…”
Section: Introductionmentioning
confidence: 99%